Ein Verfahren zur lexikographischen modellprädiktiven Regelung mit der Anwendung auf eine permanenterregte Synchronmaschine - Xaver Schnurr, Christoph (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
In classical approaches for the torque control of Permanent Magnet Synchronous Machines the torque references are converted into current references by static lookup tables which consider power losses. This procedure is dynamically suboptimal, interdependent and strongly machine-dependent. This work addresses the question: How can a Model Predictive Controller be designed to simultaneously optimize the objectives torque reference tracking and power loss minimization?